Performance of Secondary Schools from 2005-2012: An Input to Implementation of Education for All (EFA) in Region 10 - Madrid-Garabato, Melinda; Dela Rama, Juana M. (JPAIR Institutional Research, 2013)
The educational system of the Philippines aims to empower all Filipino children with access, equity and quality education. Thus, the conduct of this study gathers the profile of the public secondary schools in Region 10 in terms of enrolment both male and female, number of drop outs, number of graduates and NAT MPS Scores as an input to evaluate the performance of secondary schools on its implementation of Education for All (EFA) from year 2005-2012 in comparison to the EFA targets geared towards 2015. Data subjects for statistical treatment using Mean and Percentage rate to determine the average performance of the secondary schools in Region 10. Results have shown that the schools showed drastic increase in enrolment with a greater number of females than males. Meanwhile, NAT MPS Scores increased with 55.46 MPS in year 2012, however, secondary schools still have to work out to reach the regional EFA target of 75 with a difference of 19.54 from the actual score in 2012. Dropout Rate decreased to 4.32 and yet to work for to attain 0 dropout rate in 2015. Number of Graduates generally increased but showed a slight decrease in some school years. This shows that secondary schools in Region 10 have performed well compared to previous years, but still have to work out more towards achieving the goals of Education for All (EFA) by 2015.